The Mediating Role of CSR: Total Quality Management and Corporate Green Performance - Cristiana, Monica; Carolina, Yenni (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This study aims to determine whether Total Quality Management (TQM) influences Corporate Green Performance (CGP) and Corporate Social Responsibility (CSR), to explore whether CSR affects CGP, and to examine the mediating role of CSR between TQM and CGP. Methodology: This research is causal in nature, with data collection carried out using a questionnaire technique. The sample includes 78 companies, with respondents consisting of managers and operational staff. The data analysis technique used is Structural Equation Modeling (SEM) through the variant-based approach, Partial Least Square (PLS). Findings: TQM has a positive effect on CGP. TQM also positively influences CSR. CSR positively affects CGP and mediates the relationship between TQM and CGP. Implications: The implications of this research point to a deeper understanding of environmental impact and sustainability. Properly implemented TQM can reduce energy and resource consumption, while CSR encourages companies to consider long-term environmental impacts. Originality: Similar research has not been conducted in Indonesia, particularly in the automotive industry in Indonesia.